Ser masculinos para ser modernos (y al revés). Las narrativas sobre la civilización y género en las élites intelectuales peruanas, 1884-1915 - Grompone Velásquez, Alvaro (2023)
The paper explores the discourses around masculinity and modernity intertwined in intellectual elites’ representations during the turn of the twentieth century. The analysis uses a close-reading of certain cases cultural magazines, eulogies, literary works that illustrate such discourses. The article shows the elites’ efforts for positioning Peru within the realm of the civilized countries and as part of the advancement of Western modernity. To do so, they tried to describe the virile, strenuous, and rational character of the men than inhabited the country. On the hand, elites extolled the heroic character in terms of hegemonic masculinity of leading Peruvian figures to counter the pessimism after the War of the Pacific military defeat. In the same vein, the subsequent enthusiasm during the Aristocratic Republic was anchored in the possibilities to transform the Peruvian subjects towards greater whiteness, masculinity, and civilization.